Analisis Hubungan Islam, Spritualitas, dan Perubahan Sosial - Indra Indra (Universitas Darussalam Gontor, 2018)
Modernization has brought changes in all fields, including social field. Mankind cannot avoid the changes brought by this modernization, whether the changes are positive or negative. The problem is that the negative impacts have reduced Muslims spirituality. Modern life makes Muslims far from their religion or God. In addition, social relations between humans become loosened, and brotherhood between them fades. Modernization has indeed created a crisis of the meaning of life, spiritual emptiness, and the exclusion of religion in human life. Religion is only placed in private life and may not enter public spaces. In fact, spiritual life is believed to be able to bring and control the pattern of one’s life in a good direction. The value of spirituality is proven to be a weapon in dealing with this change, as well as a modifying factor. In Islam, the doctrine of morals (akhlâq) is a reflection of the concept of spirituality. Morals (akhlâq) are the essence of Islam and becoming medium of achieving happiness. This article will discuss the issues between the relationship, influence, and the role of religious spiritual life in social change.